THE EFFECT OF SMOKING ON THE COURSE OF THE DISEASE AND LIPID METABOLISM IN PATIENTS WITH COMMUNITY-ACQUIRED PNEUMONIA - Olena Sorokopud; Olesia Besh; Oksana Romanyshyn; Dmytro Reshot’ko (Anti-Aging Eastern Europe, 2025)
Introduction. Community-acquired pneumonia (CAP) is a disease associated with a high risk of complications and mortality, which depends on various risk factors. Smoking is one such factor that contributes to an unfavorable prognosis in various conditions. Objectives. This study aimed to assess the impact of smoking status on the course of CAP and to explore the relationship between smoking, pneumonia severity, and lipid metabolism. A total of 255 patients with CAP were included and divided into two groups: those with moderately severe pneumonia (119 patients) and those with severe pneumonia (136 patients). Among the examined patients, men predominated, and the vast majority were young. The most common complications included pleurisy, myocarditis, and renal dysfunction. Results. The incidence of complications and severe clinical course of CAP was similar in smokers and non-smokers. However, decreased body mass index (BMI) was slightly more common in smokers. Notably, low body mass was twice as frequent among smokers with severe pneumonia compared to non-smokers with severe disease. Systolic and diastolic blood pressure values were significantly lower in smokers. The number of peripheral blood leukocytes was significantly higher in smokers. C-reactive protein (CRP) levels were elevated in both groups. While the average fibrinogen levels did not differ significantly between groups, hyperfibrinogenemia (>10 g/L) was more common in smokers with severe pneumonia. Cholesterol levels were significantly lower in smokers, especially in those with severe CAP. Conclusions. The observed association between smoking and reduced cholesterol levels highlights a potential impact of smoking on lipid metabolism. Smoking cessation may improve lipid profiles and reduce the risk of severe complications in pneumonia and other diseases.